Analisis Hubungan Antara Pengetahuan Orang Tua dan Kejadian Karies Anak - Shely Oktavia Puspita Ningrum; Annafsa Zaky; Amelia Sugiarta; Emiir Hakiim; Nadine Pahlawi (Pelantar Press, 2025)
Dental caries is a prevalent health issue among preschool-aged children. At this developmental stage, children are incapable of making independent decisions; the majority of their active hours are devoted to school or parental supervision, rendering the parent's involvement essential for upholding their children's oral health and hygiene. One important aspect is parental awareness of oral health care. This study sought to examine the impact of parental awareness on dental caries in children at Kartika Kindergarten School IV-77 Malang. The study utilised an analytical observational design with a cross-sectional methodology. The sample comprised 36 children and their parents, chosen using complete sampling. Data were gathered by standardised questionnaires and clinical assessments of caries status with the DMF-T index. The Spearman correlation test was employed for data analysis. The findings indicated a substantial correlation between parental knowledge and the prevalence of dental caries in children (p 0.05). The data suggest that enhancing parental education may diminish the incidence of caries in preschool-aged children. In conclusion, the implementation of parental oral health education programs will result in healthier dental outcomes for children.